Analisis Behavioral Intention dan Use Behavior Quick Response Code Indonesian Standard (QRIS) Pada UMKM Dengan Metode UTAUT 2 di Kota Denpasar - Ni Kadek Dwi Febriani; Nengah Widya Utami; I Gusti Agung Pramesti Dwi Putri (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2023)
This study aims to determine the factors that can influence the intention to use and behavior of MSMEs in Denpasar City in using QRIS with the Unified Theory of Acceptance and Use of Technology (UTAUT) 2 Model. This research uses primary data sources with a sample of 100 respondents, taking sample using probability sampling that is simple random sampling. Test the validity and reliability test of the instrument was carried out with SmartPLS 3.0 software. Data were analyzed using the Partial Least Squares Path Modeling (PLS-SEM) method with SmartPLS 3.0 software. The results of the tests carried out show that the accepted hypothesis is that the variables that have an influence on behavioral intentions are effort expectations, facilitating conditions, hedonic motivation, and price values. The other hypothesis that is accepted is the variables that influence use behavior, namely habits and behavioral intentions. There are hypotheses that are rejected, namely performance expectancy on behavioral intention, social influence on behavioral intention, facilitating conditions on use behavior and habit on behavioral intention. Keywords: Financial Technology; QRIS; UTAUT 2; Behavior Intention; Use Behavior; PLS